Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO290 - Andrea Catalina Gebhardt; Emma Hadré; Ruth Supka; Tarik Bozkuyu; Simon Dreutter; Boris Dorschel (PANGAEA, 2023)
Multibeam data were collected with RV Sonne along the route of cruise SO290 and data acquisition was continuously monitored during the survey. Multibeam sonar system was Kongsberg EM122. SVPs were retrieved from CTD data from other working groups on board. SVPs were processed with HydrOffice SoundSpeedManager (https://www.hydroffice.org/soundspeed/main) and extended with World Ocean Atlas 13 (https://doi.org/10.7289/v5f769gt), please see environmental data (zip file). SVP data were applied during acquisition. Multibeam data are unprocessed and may contain outliers and blunders and should not be used for grid calculations and charting projects without further editing. The raw multibeam sonar data in Kongsberg multibeam processing format (.all) were recorded with Kongsberg SIS. Raw data files can be processed using software packages like CARIS HIPS/SIPS or MB-System.